Exploring the role of Mir204/211 in HNSCC by the combination of bioinformatic analysis of ceRNA and transcription factor regulation. (September 2019) - Cai, Jingyi; Yu, Yeke; Xu, Yuzi; Liu, Hao; Shou, Jiawei; You, Liangkun; Jiang, Hanliang; Han, XuFeng; Xie, Binbin; Han, Weidong
Highlights: A ceRNA network of 178 lncRNAs, 19 miRNAs and 55 mRNAs in HNSCC was built. A TF regulatory network was constructed based on the PPI network of 52 hub genes. 11 lncRNAs and 14 mRNAs were found to be survival-related in HNSCC. miR-204/211 revealed to be the promising key miRNAs in HNSCC. Abstract: Objectives: This study aimed to reveal the regulatory roles of microRNAs in head and neck squamous cell carcinoma (HNSCC) through comprehensive ceRNA, miRNA-transcription factor (TF)-hub gene network and survival analysis. Materials and methods: Expression analysis was performed using the 'edgeR' package based on The Cancer Genome Atlas database. The ceRNA network was screened by intersecting prediction results from miRcode, miRTarBase, miRDB and TargetScan. GSE30784, GSE59102 and GSE107591 from the Gene Expression Omnibus repository were chosen for cross-validation. Hub genes were identified using a protein-protein interaction network constructed by Search Tool for the Retrieval of Interacting Genes. The Transcriptional Regulatory Relationships Unraveled by Sentence-based Text mining (TTRUST) was utilized to map the miRNA-TF-Hub gene network. Patient overall survival was analyzed using the 'survival' package in R. Structural and functional analysis of miR-204/211 was based on miRbase and RNAstructure. Results: A ceRNA network of 178 lncRNAs, 19 miRNAs and 55 mRNAs was generated, and a TF regulatory network with 11 miRNAs, 11 TFs and 18 hub genes was constructed from the 52 hub genes identified through the protein–protein interaction (PPI) network. Survival analysis demonstrated that the dysregulated expression of 11 lncRNAs and 14 mRNAs was highly related to overall survival. Furthermore, miR-204 and miR-211 were significantly involved in the network with identical mature structures, indicating them as key miRNAs in HNSCC. Conclusion: This study reveals the comprehensive molecular regulatory networks centralized by miRNAs in HNSCC and uncovers the crucial role of miR-204 and miR-211, which may become potential diagnostic and therapeutic targets.